A bacterial outer membrane vesicle-based click vaccine elicits potent immune response against Staphylococcus aureus in mice - Sun, Jingjing; Lin, Xuansheng; He, Yige; Zhang, Baozhong; Zhou, Nan; Huang, Jian-dong (Frontiers in Immunology, 2023)
Staphylococcus aureus infection is a severe public health concern with the growing number of multidrug-resistant strains. S. aureus can circumvent the defense mechanisms of host immunity with the aid of multiple virulence factors. An efficacious multicomponent vaccine targeting diverse immune evasion strategies developed by S. aureus is therefore crucial for its infection control. In this study, we exploited the SpyCatcher-SpyTag system to engineer bacterial outer membrane vesicles (OMVs) for the development of a multitargeting S. aureus click vaccine. We decorated OMVs with surface exposed SpyCatcher via a truncated OmpA(a.a 1-155)-SpyCatcher fusion. The engineered OMVs can flexibly bind with various SpyTag-fused S. aureus antigens to generate an OMV-based click vaccine. The click vaccine simultaneously induced potent humoral and Th1-based cellular immune response specific for multiple antigens displayed, which afforded protection against S. aureus Newman lethal challenge in a mouse model. Our study provided a flexible and versatile click vaccine strategy with the potential for fighting against emerging S. aureus clinical isolates.